Pelaksanaan Metode-Metode Pembelajaran Pada Masa Pandemi Covid-19 di Kelas B Taman Kanak-Kanak Santa Monika Kubu Raya - Ermelinda Soo; Diana Diana; Elin B. Soemantri (Jurnal Edukasi Pendidikan Anak Usia Dini, 2022)
AbstractDuring the Covid-19 pandemic, the learning process of Santa Monika kindergarten is conducted from home, which means that both teachers and students do not attend regular school. This study aims to investigate the implementation of learning methods conducted online (learning from home) during the Covid-19 pandemic, specifically the planning, implementation and evaluation of the technique. As many as two teachers of Santa Monika Kindergarten Kubu Raya, participated as the subject. This study used a descriptive method and a qualitative approach. It was conducted in March 2021. To collect the data, the researcher used some instruments, namely observation, interview, and documentation.The results show that teachers have implemented some learning methods during the Covid-19 pandemic at Santa Monika kindergarten. They were discussion, task-based learning, play-based, demonstration, storytelling,  and singing. However, the most frequently used method was task-based learning, as the teachers quickly implemented it. Students could access the task/assignment and the learning material sent by teachers via WhatsApp application.Keywords: Learning Methods, Learning from home during the Covid-19 pandemic, task-based learning                                                  AbstrakSelama pandemic Covid-19, pembelajaran di TK Santa Monika Kubu Raya dilakukan daring, tepatnya dilakukan dari rumah. Penelitian ini bertujuan untuk mengetahui perencanaan, pelaksanaan, dan evaluasi pada metode-metode pembelajaran pada masa pandemi covid-19 yang dilaksanakan secara daring dari rumah dengan objek penelitian dua orang guru kelas B TK Santa Monika Kubu Raya. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil yang diperoleh dapat disimpulkan bahwa pelaksanaan metode-metode pembelajaran pada masa pandemi covid-19 di kelas B TK Santa Monika Kubu Raya sudah dilaksanakan dengan “cukup baik”. Beberapa metode yang digunakan selama pembelajaran daring adalah: Metode diskusi, tanya jawab, pemberian tugas, demonstrasi, bercerita, menyanyi, dan bermain. Namun, metode yang sering digunakan adalah metode pemberian tugas karena metode tersebut sangat mudah dalam pengiriman hanya berupa pesan teks melalui aplikasi WhattsApp.Kata Kunci: Metode Pembelajaran, Pembelajaran Masa  Covid-19, metode pemberian tugas